2012
DOI: 10.1128/iai.00684-12
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modulation by Group B Streptococcus Influences Host Susceptibility to Urinary Tract Infection by Uropathogenic Escherichia coli

Abstract: Urinary tract infection (UTI) is most often caused by uropathogenic Escherichia coli (UPEC). UPEC inoculation into the female urinary tract (UT) can occur through physical activities that expose the UT to an inherently polymicrobial periurethral, vaginal, or gastrointestinal flora. We report that a common urogenital inhabitant and opportunistic pathogen, group B Streptococcus (GBS), when present at the time of UPEC exposure, undergoes rapid UPEC-dependent exclusion from the murine urinary tract, yet it influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 71 publications
(77 reference statements)
5
58
0
Order By: Relevance
“…UPEC titers were similar in the presence or absence of GBS ( Fig. 1A&C ) whereas, consistent with our previous findings in young mice where we observed that GBS were rapidly cleared after co-infection with UPEC [3], GBS were rapidly cleared when UPEC were also present in the inoculum ( Fig. 1B&D ).…”
Section: Resultssupporting
confidence: 92%
“…UPEC titers were similar in the presence or absence of GBS ( Fig. 1A&C ) whereas, consistent with our previous findings in young mice where we observed that GBS were rapidly cleared after co-infection with UPEC [3], GBS were rapidly cleared when UPEC were also present in the inoculum ( Fig. 1B&D ).…”
Section: Resultssupporting
confidence: 92%
“…Recent data from Kline et al showed that the presence of S. agalactiae in the urinary tract in mice could predispose the host to other uropathogenic bacteria such as E. coli (83). Our findings suggest that ABSA strains that colonize urine more efficiently may have the potential to modify the progression of UTIs due to other causal organisms in some individuals.…”
Section: Discussionmentioning
confidence: 54%
“…Although the conventional wisdom holds that urine is sterile, the urethra connects the bladder to the outside environment, so it is not surprising that biological adaptation would enable commensal organisms to reside there. Indeed, reports of bacteriuria in normal controls are found in the literature (8,34,35). A reason why these commensal organisms are not readily detected may lie in the insensitivity of routine cultures, as shown here and by others previously (5)(6)(7)9).…”
Section: Discussionmentioning
confidence: 71%
“…Some of Kass' contemporaries criticized the use of a single threshold for diagnosing UTI in all diseases (5,6), and recently we and others also have come to question these assumptions (7)(8)(9). Biological systems fall along continuous spectra; therefore, a dichotomous judgment of no infection/significant infection using a fixed point, whether this be 10 5 , 10 4 , or 10 2 CFU ml Ϫ1 (9), may be inappropriate, especially for low-grade symptomatic infections.…”
Section: Cfu MLmentioning
confidence: 99%